Rational Design of Fe–N/C Hybrid for Enhanced Nitrogen Reduction Electrocatalysis under Ambient Conditions in Aqueous Solution - Wang, Ying; Cui, Xiaoqiang; Zhao, Jingxiang; Jia, Guangri; Gu, Lin; Zhang, Qinghua; Meng, Lingkun; Shi, Zhan; Zheng, Lirong; Wang, Chunyu; Zhang, Ziwei; Zheng, Weitao (ACS catalysis, 2019)
Developing efficient noble-metal-free catalysts for the electrochemical N2 reduction reaction (NRR) under ambient conditions shows promise in fertilizer production and hydrogen storage. Here, as a proof-of-concept prototype, we design and implement an Fe–N/C–carbon nanotube (CNT) catalyst derived from a metal–organic framework and carbon-nanotube-based composite with built-in Fe–N3 active sites. This catalyst exhibits enhanced NRR activity with NH3 production (34.83 μg·h–1·mg–1 cat.), faradaic efficiency (9.28% at −0.2 V vs RHE), selectivity, and stability in 0.1 M KOH aqueous media under mild conditions. Experimental and theoretical results both reveal that Fe–N3 species are the primary catalytically active centers for the NRR. This work provides insight into precise construction of more efficient and stable NRR electrocatalysts and further expands the possibilities of transition metal–nitrogen–carbon (M–N–C)-based nanomaterials in NRR fields.